Effect of Nutrient Media on the Growth, Physicochemical and Agar Properties of Gracilaria cliftonii Cultured in Ocean and Inland Saline Water - Kumar, Vivek; Fotedar, Ravi; Longbottom, Simon (Taylor & Francis Inc., 2011)
The effect of different nutrient media on growth, physicochemical, and agar properties of the marine algae Gracilaria cliftonii was investigated in ocean water (OW) and inland saline water (ISW). G. cliftonii fronds were cultured in 500-mL and 25-L containers with different nutrient media: Aquasol, Total, Guillard f2, Walnes, and Modified-Provasoli's Enriched Seawater in OW and ISW at 35 ppt. Specific growth rate (SGR) was higher in OW than ISW irrespective of nutrient media in both volumes. Growth of G. cliftonii in Guillard f2-supplemented OW was significantly higher than other nutrient media in both water types. Nutrient media had no influence on growth and agar properties. However, f2−supplemented OW resulted in significantly higher agar yield (58.3% db) as compared to other media. Either f2 or Walnes media are preferred nutrient sources for culturing G. cliftonii in ocean and inland saline water.